A stratigraphic, petrographic and geochemical study of the gamagara formation at the maremane dome, Northern Cape province, South Africa - Cousins, David Patrick (Rhodes University, Faculty of Science, Department of Geology, 2017)
Between 80 and 90 percent of the potential iron ore reserves in the Griqualand West basin in the Northern Cape province of South Africa is situated in the Asbesheuwels Iron-formation immediately below an unconformity that separates it from the Gamagara Formation of the Olifantshoek Supergroup. This extensive regional unconformity marks a lengthy period of non-deposition and erosion which preceded the deposition of the Gamagara Formation. Due to the nature of the intimate relationship between the shales and iron ore body, specifically on the Maremane dome, new insights into the Gamagara Formation were required. The thesis provides a renewed stratigraphic, petrographic and geochemical study on the Gamagara Formation and relates it to previous studies done on the lateral correlative Mapedi Formation, some 70 km north of the Maremane dome. The use of 10 newly available drill-cores selected from across the Maremane Dome allows for regional correlations to be made in a study which employs petrographic/mineralogical investigations using transmitted/reflected light microscopy, XRD and EPMA, complimented by traditional whole-rock geochemical analysis of majors, traces, rare earth elements and Nd isotopes. At the base of the Gamagara lie conglomerates representing an alluvial fan deposit, overlying this, shale and quartzite successions represent progradational delta lobes. The deltas are interpreted to be tide- dominated as indicated by a combination of features including: microbial mat growth, intertidal deposition in the delta top, sand bars and flaser laminations in the upward coarsening quartzite units of the delta front. Transgression is indicated by periodic transgressive lag deposits. A variety of sedimentary structures and textural features are described that can be interpreted as the results of microbial mat colonization on the sediment surface. Although in none of the described features can it irrefutably be proven that they are microbial mat deposits, the observed features are consistent with such an interpretation and should be considered indicators of possible microbial mat presence in the Gamagara Formation. Hydrothermal modifications are identified in various units of the Gamagara Formation and seem to occur as separate events. Basal white shales show mobility of Al and slight HFSE enrichments, while overlying red shales record HFSE, K and Fe enrichments. K-metasomatism has been known to occur in the underlying paleoweathering profile of the Transvaal Supergroup (Ongeluk lavas) a unit which is interpreted as the most likely provenance for the mid-to-upper shale lithofacies of the Gamagara Formation. Highly alkaline F-bearing brines had the ability to mobilize titania and fluorapatite, reset Nd isotope systematics and ultimately enriched HFSE concentrations in the red shales of the Gamagara Formation. As the same enrichment is evident in the Mapedi Formation, the event possibly represents unconformity related fluid flow on a regional scale (~140 km). Nd-isotopes record an isotopic disturbance concurrent with the HFSE enrichment and Tdm model ages suggest disruption (and enrichment) occurred between 1.73 and 1.86 Ga. Following this, Fe-addition occurred by epigenetic mechanisms similar to those of MVT-type deposits. Although gaps in the current understanding of the modifications of the Gamagara Formation exist, such events may have far reaching implications for the underlying iron ore bodies and the possibility arises that the genesis and/or epigenetic modification of the ore bodies of the Transvaal Supergroup may be casually linked to the same fluid-migration event/s.
Keywords: Iron ores -- Geology -- South Africa -- Northern Cape; Geology -- South Africa -- Northern Cape; Mineralogy -- South Africa -- Northern Cape